Fostering learning goals at work: the interplay of dispositional and workplace learning goal orientation and supervisor appraisal behavior - Schelp, Leonie; Bipp, Tanja; Gado, Sabrina; Daumiller, Martin (Psychological reports, 2023)
A workplace that emphasizes personal learning and task mastery fosters employee development and performance. However, it is yet unclear which specific factors support such a learning goal-oriented workplace. Based on research in the educational domain, we investigated the reciprocal effects of dispositional learning goal orientation, supervisor’s appraisal behavior, and a learning goal-oriented workplace. In a study with a repeated measurement design (N = 144 employees), we did not find support for an effect of supervisor’s appraisal behavior (operationalized by the perceived use of self-reference norms and constructive handling of errors by employees) on workplace learning goal orientation over time. However, we found that a dispositional learning goal orientation of employees supports a learning goal-oriented work environment. Furthermore, workplace learning goal orientation had a cross-lagged effect on dispositional learning goal orientation and supervisor’s appraisal behavior. By comparing our results from work to findings from the educational context, our results convey important theoretical implications about the construct of workplace goal orientation and suggest practical applications to foster a learning goal-oriented workplace in terms of personnel development and performance management.
Zuerst online veröffentlicht: 29. August 2023
Gesehen am 24.11.2023